Effect of bidi smoking on nasal mucociliary clearance: a comparative study. Issue 12 (20th November 2018) - Paul, B; Menon, S S; Vasthare, R; Balakrishnan, R; Acharya, S
Abstract: Objective: To compare nasal mucociliary clearance in adult non-smokers, cigarette smokers and bidi smokers using the methylene blue dye test. Methods: The study sample consisted of 20 non-smokers, 20 cigarette smokers and 20 bidi smokers (age range, 20–40 years). A single drop of the methylene blue dye was placed at the anterior end of the inferior turbinate of the participants' nasal cavity. The distance travelled by the methylene blue in 15 minutes inside the nasal cavity was measured. Nasal mucociliary clearance of the three groups was compared using the Kruskal Wallis test. Results: Nasal mucociliary clearance was significantly decreased in bidi smokers as compared to cigarette smokers and non-smokers ( p < 0.05). Multivariate analysis revealed a significant association between nasal mucociliary clearance and bidi smoking, number of cigarettes or bidis smoked per day, and pack-years (all p < 0.05). Conclusion: Nasal mucociliary clearance measurement is a simple and useful index for assessing the effect of smoking on the mucociliary activity of nasal mucosa.